Risk Modeling Concepts Relating to the Design and Rating of Agricultural Insurance Contracts - Goodwin, Barry K.; Mahul, Olivier (World Bank, Washington, D.C., 2013)
The authors identify the key issues and concerns that arise in the design and rating of crop yield insurance plans, with a particular emphasis on production risk modeling. The authors show how the availability of data shapes the insurance scheme and the ratemaking procedures. Relying on the U.S. experience and recent developments in statistics and econometrics, they review risk modeling concepts and provide technical guidelines in the development of crop insurance plans. Finally, they show how these risk modeling techniques can be extended to price risk in order to develop crop revenue insurance schemes.